Spatio-temporal Modelling of Accessibility to Train Stations for Park and Ride (PnR) Users - Lin, Ting (Curtin University, 2017)
Accessibility has been of critical importance to physical planning over the past 60 years. This study mainly focuses a spatial methodology framework to understand measure and model the Park and Ride (PnR) users’ accessibility to train stations, specifically including the characteristics of catchment areas, directional accessibility to train stations, spatial modelling of train stations’ catchment areas, and spatio-temporal modelling of accessibility to train stations.